Oilfield Chemistry - Dai, Caili; Zhao, Fulin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book provides comprehensive information on the youngest member of the petroleum sciences family: Oilfield Chemistry, proposes the chemical agents for addressing current problems, and explains the functions, mechanisms and synergistic effects of various chemical agents.
Part 1 Drilling Chemistry Chapter 1 Clay Minerals -- Chapter 2 Drilling Fluid Chemistry -- Chapter 3 Cement Slurry Chemistry Part 2 Oil Production Chemistry Chapter 4 Chemical Flooding and Miscible Flooding -- Chapter 5 Profile Control and Water Shutoff -- Chapter 6 Viscosity Reduction of Heavy Oil -- Chapter 7 Acids and Additives used in Acidizing -- Chapter 8 Fracturing Fluids and Fracturing Fluid Additives -- Chapter 9 Sand Control in oil and water wells -- Chapter 10 Wax Control and Removal in Oil Well Part 3 Gathering and Transportation Chemistry Chapter 11 Corrosion and Anti-Corrosion of Buried Pipeline -- Chapter 12 Demulsification of the Emulsified Crude Oil and Defoaming of the Foaming Crude Oil -- Chapter 13 Pour Point Depression Transportation and Drag-Reduction Transportation of Crude Oil -- Chapter 14 Natural Gas Treatment -- Chapter 15 Oilfield Wastewater Treatment.
Keywords: Chemistry, Technical; Cogeneration of electric power and heat; Fossil fuels; Engineering geology; Geochemistry; Environment; Industrial Chemistry; Fossil Fuel; Geoengineering; Geochemistry; Environmental Sciences